Predicted National, State and Educational Issues Derived from a Modified Delphi Study for the Formulation of Long-Range Educational Policies - Robert R. Simmons; Nancy E. Kaldor (Educational Considerations, 1983)
Educational leaders must begin to look ahead (not just to next year, but into the future) and they must begin to plan accordingly.